Influence of rare earth oxides on kinetics and reaction mechanisms in CMAS silicate melts. Issue 14 (November 2019) - Perrudin, F.; Vidal-Sétif, M.H.; Rio, C.; Petitjean, C.; Panteix, P.J.; Vilasi, M.
Abstract: Dissolution of different rare earth oxides RE2 O3 and cyclosilicate Ca3 RE2 (Si3 O9 )2 was studied at 1200 °C in a pseudo-ternary CAS melt. This investigation is relevant to CMAS resistant thermal barrier coatings (TBC) used in aircraft engines. CMAS is a generic term for the molten siliceous deposits resulting from the ingestion of mineral particles with the intake air. The aim was to assess the influence of the rare earth on the reaction kinetics, solubility limits and underlying phase equilibria in a model CAS melt. RE2 O3 (RE = Nd, Sm, Gd, Dy and Yb) were selected to span a wide range of trivalent lanthanide sesquioxides and Lewis basicities. Powders dispersed in CAS glass-beads were reacted at 1200 °C and quenched after several durations. All the RE2 O3 led to the formation of metastable apatite, and then to stabilization of cyclosilicate in CAS. Disilicate Yb2 Si2 O7 was also obtained in Yb2 O3 bead-sample during early-stage of interaction. However, RE2 O3 oxide basicity has a direct influence on silicates (apatite, disilicate and cyclosilicate) solubility limits in CAS, on RE-apatite crystal growth as well as on induction time for RE-cyclosilicate nucleation. The results are discussed in the light of crystal chemistry, thermodynamic considerations and RE cation field strength (Z/r²) which is alternative to define oxide basicity.